2009
DOI: 10.1111/j.1469-0691.2008.02112.x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Lactobacillus-containing vaginal tablets in the treatment of symptomatic bacterial vaginosis

Abstract: The purpose of this study was to determine the effectiveness of Lactobacillus-containing vaginal tablets in the treatment of bacterial vaginosis (BV) and in the restoration of a healthy vaginal flora. Thirty-nine women with BV were enrolled in a double-blind, placebo-controlled clinical trial. Patients received either one Lactobacillus-containing tablet or placebo daily for 7 days. Clinical criteria, vaginal Gram stain scores and symptoms were compared with those at the initial visit and those at completion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
118
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 158 publications
(131 citation statements)
references
References 49 publications
2
118
0
4
Order By: Relevance
“…Clinical trials in which patients were administered oral capsules, reported a positive effect of the treatment on BV [39, 41-43, 49, 56]. Vaginal probiotic tablets were reported to be effective in alleviating BV symptoms and decreasing its recurrence [1,4,52,53]. Vaginal capsules have also been reported to efficiently ease BV symptoms in some studies [3,42,50,55].…”
Section: Administration Vehiclesmentioning
confidence: 99%
See 3 more Smart Citations
“…Clinical trials in which patients were administered oral capsules, reported a positive effect of the treatment on BV [39, 41-43, 49, 56]. Vaginal probiotic tablets were reported to be effective in alleviating BV symptoms and decreasing its recurrence [1,4,52,53]. Vaginal capsules have also been reported to efficiently ease BV symptoms in some studies [3,42,50,55].…”
Section: Administration Vehiclesmentioning
confidence: 99%
“…Probiotics are believed to protect the host against infections by means of several mechanisms including: [1] occupation of specific adhesion sites at the epithelial surface of the urinary tract; [2] maintenance of a low pH and production of antimicrobial substances like acids, hydrogen peroxide, and bacteriocins; [3] degradation of polyamines; and [4] the production of surfactants with antiadhesive properties [21,42].…”
Section: Probiotic and Bacterial Vaginosismentioning
confidence: 99%
See 2 more Smart Citations
“…Так, D. Parent et al (1996) в 88 % случаев наблюдали нормализацию микрофлоры влага-лища в группе женщин, лечение БВ у которых проводилось путем интравагинального введе-ния капсул, содержащих L. acidophilus, в тече-ние 4 недель [65]. Позднее было проведено два клинических исследования с использованием пробиотиков, содержащих L. rhamnosus GR-1 и L. reuteri RC-14, в сравнении с применением метронидазола [66] [67], -с группой плацебо. Показано дву-кратное снижение заболеваемости БВ в группе с интравагинальным применением пробиоти-ков в сравнении с группой, в которой исполь-зовался метронидазол (65 и 33 % случаев соот-ветственно) [66], и выявлена эффективность лечения в 50 % случаев в группе с применением пробиотиков, содержащих L. brevis, L. salivarius и L. plantarum, в сравнении с группой плацебо (6 %) [67].…”
unclassified